Pseudohomophones as brand names: Prioritising the emotionally interesting homophone. (10th September 2018) - Ilicic, Jasmina; Baxter, Stacey; Kulczynski, Alicia
Abstract : Purpose: The purpose of this study is to introduce the homophone emotional interest superiority effect in phonological, or sound-based, priming, whereby pseudohomophone brand names (i.e. non-words that are pronounced identically to English words, for example, Bie) prime brand meaning associated with the member of the homophone pair that is emotionally interesting (i.e. Bie will be prime brand avoidance (purchase) when consumers are emotionally interested in the homophone bye [buy]). Design/methodology/approach: Studies 1 and 2 examine the effect of homophone emotional interest on brand judgements and behaviours. Study 3 investigates the role of boredom with the brand name in attenuating the homophone emotional interest superiority effect. Findings: Findings indicate that pseudohomophone brand names prime brand judgements and behaviours associated with the word from the homophone pair that evokes emotional interest. Study 2 provides further evidence of homophone emotional interest as the process influencing brand judgements and behaviours. Study 3 establishes that the effect of pseudohomophone brand names on brand judgements weaken when boredom with the brand name is induced. Research limitations/implications: This study is limited, as it focuses only on fictitious brands and methodologically creates boredom in a way in which may not be typical of what would be experienced in the real world. Practical implications: This study has important implications for brand managers in the development of new brand names and in prioritising the intended homophone pair from a pseudohomophone brand name to influence consumer judgements and behaviours. Originality/value: This study introduces and provides evidence of a homophone emotional interest superiority effect. This study also identifies a condition under which the homophone emotional interest superiority effect is attenuated.